2011
DOI: 10.1080/00221325.2010.528077
|View full text |Cite
|
Sign up to set email alerts
|

The Reciprocal Relations Between Teachers’ Perceptions of Children's Behavior Problems and Teacher–Child Relationships in the First Preschool Year

Abstract: To examine the reciprocal relations between teacher-child relationships and children's behavior problems, the authors analyzed cross-lagged longitudinal data on teacher-child relationships and children's internalizing and externalizing problems using a structural equation modeling approach. The homeroom teachers of 105 first-year preschoolers aged 2-3 years filled in the Student-Teacher Relationship Scale and the Child Behavior Checklist/2-3, first at 3 months after the children's preschool entrance and then a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
99
7
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(130 citation statements)
references
References 31 publications
21
99
7
3
Order By: Relevance
“…In line with studies in mainstream education (De Laet et al 2014;Zhang and Sun 2011) we found that teacher-child conflict increased children's disobedience throughout the school year. On the other hand, our finding that a more positive teacher-child relationship didn't reduce boys' disobedience was not in line with some previous studies in mainstream education (Baker 2006;Hughes et al 1999).…”
Section: Developmental Links Between Disobedience and Social Relationsupporting
confidence: 71%
See 2 more Smart Citations
“…In line with studies in mainstream education (De Laet et al 2014;Zhang and Sun 2011) we found that teacher-child conflict increased children's disobedience throughout the school year. On the other hand, our finding that a more positive teacher-child relationship didn't reduce boys' disobedience was not in line with some previous studies in mainstream education (Baker 2006;Hughes et al 1999).…”
Section: Developmental Links Between Disobedience and Social Relationsupporting
confidence: 71%
“…Indeed, a study by Ladd et al (1999) shows that teacher-child conflict and peer rejection were more important predictors of children's classroom adjustment than teacher-child closeness and peer acceptance. Also, a study by Zhang and Sun (2011) shows that teacher-child conflict was more strongly related to children's externalizing behavior than teacher-child closeness. For that reason, we will examine two models: a positive relationships model including teacher-child closeness and peer acceptance, and a negative relationships model including teacher-child conflict and peer rejection.…”
Section: Advancing Current Knowledge: Some Conceptual and Methodologimentioning
confidence: 99%
See 1 more Smart Citation
“…A reciprocal transaction starting with teacher-child conflict in wave 1 was not observed. In sum, both bidirectional and recursive effects have been demonstrated for teachers, but only with regard to conflict with children (as reported by teachers), and not with regard to reported closeness (Doumen et al, 2008;Zhang & Sun, 2011).…”
Section: The Transactional Modelmentioning
confidence: 97%
“…Relations between these two constructs and children's EB have been shown (Birch & Ladd, 1998;Hamre & Pianta, 2001;Silver, Measelle, Armstrong, & Essex, 2005). Bidirectional relations were tested in a two-wave study encompassing preschoolers from the general community (Zhang & Sun, 2011). Teachers reported about teacher-child QR and children's EB at 3 months after starting school and at the end of the school year among children aged 2-3 years.…”
Section: The Transactional Modelmentioning
confidence: 99%